Comparing 3 Different Techniques of Patella Fracture Fixation and Their Complications. (28th February 2019) - Shea, Graham Ka-Hon; Hoi-Ting So, Karen; Tam, Kin-Wai; Yee, Dennis King-Hang; Fang, Christian; Leung, Frankie
Introduction: Patella fractures managed by fixation with metal implants often cause local soft tissue irritation and necessitate implant removal. An alternative is to utilize suture-based fixation methods. We have adopted suture and hybrid fixation in the routine management of patella fractures. Here, we compare the results of 3 fixation techniques. Materials and Methods: Eighty-seven eligible patients underwent patella fracture fixation over a 3-year period. As determined by fracture configuration, patients received (1) suture fixation (transosseous sutures and figure-of-eight tension banding with FiberWire), (2) hybrid fixation (transosseous FiberWire sutures and metal tension banding), or (3) metal fixation. Primary outcome measures included reoperation rate and soft tissue irritation. Secondary outcomes included surgical complications, radiological, and functional parameters. Results: Reoperation rate was highest for metal fixation (25/57, 43.9%) and lowest for suture fixation (2/13, 15.4%). Soft tissue irritation necessitating implant removal was the predominant reason for reoperation and was significantly less prevalent following suture fixation (1/13, 7.7%, P < .01). Hybrid fixation resulted in similar rates of soft tissue irritation (6/17, 35.3%) and implant removal (7/17, 41.2%) as compared to metal fixation. There was a significant increase in patella baja (13/17, 76.5%) and reduction in Insall-Salvati ratio (0.742; 95% confidence interval: 0.682-0.802) following hybrid fixation as compared to the other 2 fixation methods ( P < .05). Discussion: Suture fixation results in the least amount of soft tissue irritation and lowest reoperation rate, but these advantages are negated with the addition of a metal tension band wire. Hybrid fixation also unbalances the extensor mechanism. Conclusion: Patients should be counseled as to the expected sequelae of their fixation method. Suture fixation is the favored means to fix distal pole fractures of the patella. An additional metal tension band loop may confer additional stability but should be applied with caution.